(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract: This Study Aims To Clarify The Role Of Packaging Design In Influencing The Purchasing Behavior Of The Consumer, A Comparative Study Between Chanel And Givenchy Perfume, By Distributing Questionnaires To A Sample Limited To 60 Females, And This Was Done In July 2021, By Studying The Packaging In Terms Of Quality And The Shape And Design And Their Role In Attracting The Consumer, And This Study Concluded That The Packaging Is Not Enough For Repurchase And That The Brand Plays The Largest Role In Making The Purchase, Which Indicates That The Latter Contributes More To Attracting The Consumer. Keywords: Packaging, Packaging Design, Consumer, Primary Packaging, Consumer Behavior